The Burdensharing Debate - Duke, Simon. author. aut Link
XXII, 277 p.
Keywords: Examines critically the history and assumptions behind the divisive question of allied contributions to the common defence. It looks at the methodology of the burdensharing debate and focuses on political, economic and military ramifications of the debate.